RECURRENCE OF HERPES ZOSTER IN AN IMMUNOCOMPETENT ADULT MALE - Raza, Naeem; Iqbal, Pervaiz; Anwer, Javed (Journal of Ayub Medical College Abbottabad, 2005)
Repeated and disseminated eruptions of herpes zoster are frequently detected in immunocompromised patients, but are rare in immuno-competent individuals. We report a case of recurrent herpes zoster in a young healthy male, who redeveloped herpes zoster in a different dermatome after one year. Keywords: Herpes Zoster, Recurrent, Immunocompetent.